Synthesis and Antibacterial Activities of Halogenated Hydroxy Diphenyl Ether Derivatives - Min Chen1, Guang; Yang1, Xiu; Chun Li2, Jian; Wu1, Kai-Qun; Wang1, Yu-Liang; Chen2, Tian (Asian Journal of Chemistry, 2013)
Seven halogenated hydroxy diphenyl ether derivatives have been synthesized, 6 of them are new compounds and their structures were identified by 1H NMR, HR-MS and IR spectra. The antibacterial activities of all the present compounds were tested via the agar-well diffusion method in vitro in the concentration of 50 μg/mL. The results showed that most of the new compounds exhibited antibacterial activities against the tested bacterium.